Trisomy 10p syndrome owing to maternal pericentric inversion. - Ohba, K (1990)
A female infant with karyotype 46,XX,rec(10),dup p inv(10)(p11.2q25.2)mat is presented. She had both duplication of 10p and deletion of distal 10q, but only had the constellation of specific features characteristic of duplication of 10p.